2004
DOI: 10.1001/archotol.130.9.1029
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Computed Tomography in Pediatric Chronic Rhinosinusitis

Abstract: To determine the accuracy of computed tomography (CT) in the diagnosis of pediatric chronic rhinosinusitis (CRS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 16 publications
1
79
0
6
Order By: Relevance
“…1410 It is also believed that some children may have chronic adenoiditis with no CRS because symptoms of the 2 entities cannot be distinguished without CT scan of the sinuses. 1411 There is controversy whether the size of the adenoids matter in children with PCRS. Children with symptoms of RS who had a CT scan of the sinuses and underwent an adenoidectomy were investigated and results showed no correlation between the size of the adenoids and the severity of disease on CT scan.…”
Section: Xib2 Pediatric Crs: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…1410 It is also believed that some children may have chronic adenoiditis with no CRS because symptoms of the 2 entities cannot be distinguished without CT scan of the sinuses. 1411 There is controversy whether the size of the adenoids matter in children with PCRS. Children with symptoms of RS who had a CT scan of the sinuses and underwent an adenoidectomy were investigated and results showed no correlation between the size of the adenoids and the severity of disease on CT scan.…”
Section: Xib2 Pediatric Crs: Pathophysiologymentioning
confidence: 99%
“…In a study comparing 66 children with CRS symptoms to 192 control children having CT imaging for nonsinus indications, it was noted that children with a LM score of 5 or more had a sensitivity and specificity of 86% and 85%, respectively, of having CRS, whereas a CT score of 2 had an excellent negative predictive value of CRS, making the diagnosis of chronic adenoiditis more likely. 1411 It should be noted that use of CT should be reserved for when surgery is being considered and not utilized routinely to make the diagnosis of PCRS.…”
Section: Xib3 Pediatric Crs: Diagnosismentioning
confidence: 99%
“…6,8 However, to exclude false positives, we considered scans with a score <3 negative, unless the disease distribution by CT correlated anatomically with the location of the patient's symptoms (eg, chronic unilateral frontal pressure in a patient with partial opacity of the ipsilateral maxillary and anterior ethmoid sinus, sans sinus disease elsewhere). In the pediatric population Bhattacharyya et al 9 found a Lund-Mackay score of ≥5 yields a sensitivity and specificity of 86% and 85%, respectively. No comparable study has been done in adults, so there continues to be no accepted cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were included in the study according to the following inclusion criteria: age >16 years, satisfied diagnostic criteria (clinical symptom criteria and radiographic criteria) for CRS without nasal polyposis, failed standard medical management, underwent standard ESS with tissue submitted for histopathology, and pathology was available for review. 6,7 All patients completed a preoperative Rhinosinusitis Symptom Inventory (RSI), cataloging their symptom severity scores for the major and minor symptoms of CRS as well as their medication usage with respect to CRS. 1 For each patient, standard demographic information was collected and their scores on the individual elements of the RSI and RSI symptom domains (domains: nasal, facial, oropharyngeal, systemic, and total symptoms) were tabulated and calculated.…”
Section: Methodsmentioning
confidence: 99%